Individual attitudes towards trade: Stolper-Samuelson revisited - Ina C. Jäkel; Marcel Smolka (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
This paper studies to what extent individuals form their preferences towards trade policies along the lines of the Stolper-Samuelson logic. We employ a novel international survey data set with an extensive coverage of high-, middle-, and low-income countries, address a subtle methodological shortcoming in previous studies and condition on aspects of individualenlightenment. We find statistically significant and economically large Stolper-Samuelson effects. In the United States, being high-skilled increases an individual's probability of favoring free trade by up to twelve percentage points, other things equal. In Ethiopia, the effect amounts to eight percentage points, but in exactly the opposite direction.
urn:nbn:de:bsz:21-opus-56580
Keywords: F11; F13; 330; Trade policy; Voter preferences; Political economy